PENINGKATAN HASIL BELAJAR SOAL CERITA PENJUMLAHAN PECAHAN DENGAN LANGKAH-LANGKAH POLYA DI SEKOLAH DASAR - Masria, Ali (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
In this study, the authors applied the learning Polya steps to improve student learning outcomes. This study aimed to describe the planning, execution, and improved learning outcomes. This research was classroom action research. Using qualitative and quantitative approaches. Subjects were teachers and students of class IV Elementary School District 04 Biaro Ampek Angkek. In the first cycle of teachers in designing learning skills 69.5%, 69.5% showed teacher activity and student activity 62.5%. Meanwhile, the second cycle was seen to rise. The ability of teachers in designing learning to 86%. activity to 87.5% of teachers, student activity to 83.5%. In short, action research using Polya steps to improve student learning outcomes. Kata Kunci : hasil belajar, soal cerita penjumlahan pecahan, dan langkah-langkah polya